Найдите наименьшее решение уравнения 11^(x^2-4x-5)=6^(x^2-4x-5)

nastgoliakova nastgoliakova    3   27.09.2019 02:00    0

Ответы
yuraseven77 yuraseven77  21.08.2020 16:45

Используемые свойства:

1) \frac{a^m}{b^m} = (\frac{a}{b}) ^m

2)a^0 = 1


11^{x^2-4x-5} = 6^{x^2-4x-5} | : 6^{x^2-4x-5}\\ \frac{11^{x^2-4x-5}}{6^{x^2-4x-5}} = \frac{6^{x^2-4x-5}}{6^{x^2-4x-5}} \\\\ (\frac{11}{6})^{x^2-4x-5} = (\frac{11}{6}) ^0\\ \\ x^2-4x-5 = 0\\ x_1 = -1; x_2 = 5

ответ: -1

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра